2011
DOI: 10.1002/ijc.26314
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor genes and their association with colon and rectal cancer development and prognosis

Abstract: Toll-like receptors (TLR) are mediators of inflammation in the gut and potentially important modulators of colon and rectal cancer risk. We use data from a population-based study of incident colon cancer cases (n=1,555) and controls (n=1,956) and rectal cancer cases (n=754) and controls (n=959). We evaluate genetic variation in TLR2 (6 SNPs), TLR3 (4 SNPs), and TLR4 (8 SNPs) with risk of developing colon or rectal cancer and survival after diagnosis. TLR3 rs11721827 was associated with rectal cancer (OR 1.27 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 26 publications
1
80
0
1
Order By: Relevance
“…34), we further investigated the relationship between Hic1 and Tlr2 expression. First, we generated a Tlr2-Luc reporter by subcloning genomic DNA harboring the Tlr2 promoter region before the luciferase sequence.…”
Section: Identification Of Tlr2 As a Novel Target Gene Repressed By Hmentioning
confidence: 99%
“…34), we further investigated the relationship between Hic1 and Tlr2 expression. First, we generated a Tlr2-Luc reporter by subcloning genomic DNA harboring the Tlr2 promoter region before the luciferase sequence.…”
Section: Identification Of Tlr2 As a Novel Target Gene Repressed By Hmentioning
confidence: 99%
“…The frequency of the Tlr2-196-174 del allele was significantly higher in patients with HCV-associated HCC. This phenomenon was noted not only in HCC but also in gastric cancer (28), colon cancer (29), and prostate cancer (30), further indicating the importance of TLR2 in tumor immunosurveillance.…”
Section: Discussionmentioning
confidence: 83%
“…The reason was that ALL did not belong to solid tumors. Furthermore, for the +597T>C polymorphism (rs3804099), we updated two new studies (Kim et al, 2012;Slattery et al, 2012), and no significant association was found in Asians or Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, a total of 14 studies were finally identified (Nieters et al, 2006;Etokebe et al, 2009;Purdue et al, 2009;Ashton et al, 2010;Balistreri et al, 2010;Gast et al, 2011;Zeng et al, 2011;Junjie et al, 2012;Kim et al, 2012;Nischalke et al, 2012;Slattery et al, 2012;Yang et al, 2012;Pimentel-Nunes et al, 2013). For the +597T>C polymorphism (rs3804099), 8 studies were available, including a total of 3987 cases and 5079 controls.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%